2016
DOI: 10.3127/ajis.v20i0.1350
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of how the Australian brewing industry influence consumers on Twitter

Abstract: In this paper we develop and test hypotheses around organisations' behaviour on social media and its effect on consumers' responses. We draw on the notion of the market maven to underpin the research and suggest that organisations on social media need to focus on acting in a maven-like manner in order to influence audiences in Twitter. We collected data from the Twitter accounts of the entire brewing industry in Australia, analysing organisational postings and their impact on influence (follower numbers, retwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 52 publications
0
5
2
3
Order By: Relevance
“…However, the results obtained here also seem to contradict what other authors have found, especially with regard to publication components and publication time slots [32,63]. Aleti et al [32] show that a correct exploitation of publication components, such as hashtags and mentions, significantly improves customer engagement.…”
Section: Answers To the Posed Research Questionscontrasting
confidence: 95%
See 3 more Smart Citations
“…However, the results obtained here also seem to contradict what other authors have found, especially with regard to publication components and publication time slots [32,63]. Aleti et al [32] show that a correct exploitation of publication components, such as hashtags and mentions, significantly improves customer engagement.…”
Section: Answers To the Posed Research Questionscontrasting
confidence: 95%
“…However, the results obtained here also seem to contradict what other authors have found, especially with regard to publication components and publication time slots [32,63]. Aleti et al [32] show that a correct exploitation of publication components, such as hashtags and mentions, significantly improves customer engagement. Sabate et al [63], on the other hand, regarding publication time slots, conclude that messages published during business hours are more likely to receive comments and therefore that publication time influences the amount of interactions.…”
Section: Answers To the Posed Research Questionscontrasting
confidence: 95%
See 2 more Smart Citations
“…The paper uses SMA to obtain a generic and bigger picture of citizens' opinions to analyze scheme-related posts. The posts were collected from Twitter, a microblogging SM platform that contains various metadata information that can be collected cost-effectively (Aleti et al, 2016;Rathore et al, 2017;Aswani et al, 2018a;Grover et al, 2018).…”
Section: Introductionmentioning
confidence: 99%